A novel investigation of the effect of different concentrations of methacrylic acid on the dose response of MAGAT gel dosimeter in intraoperative radiotherapy. (February 2021) - Nezhad, Zahra Alyani; Geraily, Ghazale; Parwaie, Wrya; Zohari, Shahin
Abstract: Purpose: High dose prescription in one treatment session of intraoperative radiotherapy (IORT) requires precise monitoring of the delivered dose. Methacrylic acid, gelatin and tetrakis phosphonium chloride (MAGAT) gel with superior dose sensitivity and dose resolution seems to be a suitable tool for 3 dimensional dose verification of IORT. In the current study, the dose response of MAGAT gel dosimeter with varying concentrations of methacrylic acid (MAA) was investigated. Finally, the MAGAT with optimal concentration was subjected to dose rate and energy dependency measurements. Methods: MAGAT gel with different concentrations of 3, 5, 6, 8 and 10% was manufactured and irradiated with 50 keV produced by IORT. Gel vials were read out by MRI and R 2 responses were plotted against dose. Dose rate and energy dependency of optimum MAGAT gel were assessed by irradiation by a VARIAN linear accelerator using various dose rates of 30, 40 and 50 cGy/min and diverse photon energies of 6 and 18 MV as well as 50 keV of IORT. Results: MAGAT with a concentration of 8% MAA, exhibited a high-dose response and dose sensitivity of 5.16 Gy −1 s −1 in irradiation by IORT. Moreover, its response was independent of low dose rates (30, 40 and 50 cGy/min) and mega-voltage energies (p > 0.05). However, there was a significant difference between the R 2 -dose response of MAGAT irradiated by mega-voltage (6 and 18 MV) and 50 keV energy of IORT. Conclusion: MAGAT is an effective tool to investigate three dimensional dose distributions of IORT independent of dose rates used in X-ray IORT. Moreover, its response is energy independent over mega-voltage energies. Highlights: The first application of methacrylic acid (MAA) based gel dosimeters in IORT. MAGAT gel containing 8% MAA is suitable for dosimetry purposes in IORT. MAGAT has no dose rate dependency over low dose rates applied in IORT. MAGAT has no energy dependence over mega voltage energies. MAGAT gel exhibits great sensitivity to kilovoltage energy photons.